Those who save us - Blum, Jenna (Orlando, Florida : Harcourt, 2005)
A German girl in love with a Jewish man is forced to flee her father's house and finds a home and work in the bakery that supplies pastries for the officers of Buchenwald, where she is noticed by the highest ranking officer. Years later, she still will not relate her war experiences, and her daughter begins a deeper investigation that unearths a heartbreaking secret.
Keywords: World War, 1939-1945 -- Underground movements -- Fiction; Domestic fiction